2002
DOI: 10.1093/embo-reports/kvf022
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for membrane rafts in the initiation of Fas/CD95‐triggered cell death in mouse thymocytes

Abstract: Fas, a member of the tumor necrosis factor receptor family, can upon ligation by its ligand or agonistic antibodies trigger signaling cascades leading to cell death in lymphocytes and other cell types. Such signaling cascades are initiated through the formation of a membrane death-inducing signaling complex (DISC) that includes Fas, the Fas-associated death domain protein (FADD) and caspase-8. We report here that a considerable fraction of Fas is constitutively partitioned into sphingolipid-and cholesterol-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
171
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 28 publications
12
171
2
1
Order By: Relevance
“…Most of these studies suggested that the formation of ceramide-enriched membrane platforms is initiated within small cholesterol-and sphingolipid-enriched membrane rafts. The notion that rafts are important for the induction of apoptosis is supported by several recent studies demonstrating that destruction of these membrane rafts prevents CD95 clustering, recruitment of FADD and caspase 8 and apoptosis by CD95 (Cremesti et al, 2001;Grassme et al, 2001b;Hueber et al, 2002;Scheel-Toellner et al, 2002). However, our studies go far beyond the finding that rafts are involved in apoptosis and suggest a mechanism how small rafts in resting cells can be transformed into a signaling unit that transmits signals from out to inside of the cell.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Most of these studies suggested that the formation of ceramide-enriched membrane platforms is initiated within small cholesterol-and sphingolipid-enriched membrane rafts. The notion that rafts are important for the induction of apoptosis is supported by several recent studies demonstrating that destruction of these membrane rafts prevents CD95 clustering, recruitment of FADD and caspase 8 and apoptosis by CD95 (Cremesti et al, 2001;Grassme et al, 2001b;Hueber et al, 2002;Scheel-Toellner et al, 2002). However, our studies go far beyond the finding that rafts are involved in apoptosis and suggest a mechanism how small rafts in resting cells can be transformed into a signaling unit that transmits signals from out to inside of the cell.…”
Section: Discussionsupporting
confidence: 72%
“…Rafts are organized membrane domains mainly composed of glycosphingolipids, sphingomyelin, cholesterol and specific membrane proteins (Simons and Ikonen, 1997;Brown and London, 1998). Several studies indicated that rafts are required to cluster CD95 and to recruit FADD, caspase 8 and 3 to CD95 upon stimulation (Grassme et al, 2001bHueber et al, 2002;Scheel-Toellner et al, 2002;Delmas et al, 2003;Aouad et al, 2004;Eramo et al, 2004). Accordingly, disruption of rafts prevented CD95-induced apoptosis, at least in most cells (Grassme et al, 2001b;Cremesti et al, 2001;Hueber et al, 2002;Scheel-Toellner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…8,17 Biochemically, these nanodomains can be isolated from cell lysate thanks to their insolubility in non-ionic detergent, and known as detergentresistant membrane nanodomains (DRMs). We subjected SW480 Fas WT cells to DRM isolation and showed that 27% of Fas is located in the DRM fractions, whereas only 14% when DHHC7 is knocked down (Figure 3d), validating by a genetic approach that DHHC7 is allowing Fas to be targeted to specific membrane nanodomains probably by palmitoylation.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 At the molecular level, we and others already reported that the pro-death role of Fas palmitoylation relies on (i) the formation of supramolecular Fas aggregates 9 and (ii) Fas targeting in nanodomains enriched in cholesterol and glycosphingolipids, which is a prerequisite for proper activation of Fas-induced cell death. 8,[17][18][19][20][21] In these domains and upon FasL binding, palmitoylation allows Fas to recruit ezrin and actin cytoskeleton that lead to Fas internalization and transmission of death signal. 8 We thus aimed at understanding how Fas palmitoylation is regulated.…”
mentioning
confidence: 99%
“…6 Although not all cell types show the raft-dependency of CD95/Fas clustering, 7,8 in lymphocytic cells, the GEM-dependency of the initiation of receptor clustering and signaling was demonstrated by using cholesterol depleting agents, such as methyl-b-cyclodextrin (MbCD). 9 In addition, it was hypothesized 10,11 that a portion of intracellular GD3 can play a role in apoptotic machinery. Activation of death receptors (CD95/Fas, TNFa receptor) induces an intracellular flow of GD3, probably carried entirely by raft-containing vesicular transport.…”
Section: Introductionmentioning
confidence: 99%